Reevaluation of the Layered Anatomy of the Forehead: Introducing the Subfrontalis Fascia and the Retrofrontalis Fat Compartments. Issue 3 (10th January 2022) - Ingallina, Fabio; Frank, Konstantin; Mardini, Samir; Gavril, Diana L.; Hernandez, Claudia A.; Benslimane, Fahd; Gotkin, Robert H.; Davidovic, Kristina; Moellhoff, Nicholas; Cotofana, Sebastian
Abstract : Background: Novel imaging methods have provided new insights into the layered anatomy of the forehead. This study seeks to critically reevaluate the layered anatomy of the forehead by using ultrasound imaging and cadaveric dissection to provide an accurate anatomical description that can be used to guide safer surgical and minimally invasive frontal procedures. Methods: This study used ultrasound imaging in a sample of 20 volunteers (12 female and eight male volunteers; aged 35.25 ± 4.2 years; body mass index, 24.28 ± 3.5 kg/m 2 ) and cadaveric dissections of 16 body donors (12 female and four male body donors; aged 72.76 ± 9.5 years) to reevaluate the layered anatomy of the forehead. Layer-by-layer dissections and ultrasound-based measurements of the frontal structures guided conclusions. Results: The following layered arrangement was identified: layer 1, skin; layer 2, superficial fatty layer; layer 3, suprafrontalis fascia; layer 4, orbicularis oculi and frontalis muscle (same plane); layer 5, a homogenous layer of fat [preseptal fat (in the upper eyelid), retro-orbicularis fat (deep to the orbicularis oculi muscle), and retro-frontalis fat (deep to the frontalis muscle); layer 6, subfrontalis fascia; layer 7, preperiosteal fat within the prefrontal space in the lower forehead and deep compartments in the upper forehead; and layer 8, periosteum. Conclusions: The results of this study add to the current understanding of the layered arrangement of the forehead. The combination of ultrasound imaging and cadaveric dissections provided evidence for a continuous fatty layer deep to the frontalis muscle.